The Influence of The Chief Engineer's Leadership Style on The Performance of Crew Members in The Engine Room - Agraprana Rafasya; Monika Retno Gunarti; Elly Kusumawati; Shofa Dai Robbi; Agus Prawoto (International Journal of Science and Environment (IJSE), 2026)
Human resource management in ship engine rooms faces challenges such as low productivity and high turnover due to the ineffective leadership style of the chief engineer. This study aims to analyze the influence of the chief engineer's leadership style on the performance of crew members (ABK) in the engine room. Using a quantitative explanatory approach with a descriptive survey design, the population includes all crew members in the engine room of the marine practice ship Polytechnic of Shipping Surabaya, with a sample of 35 respondents through purposive sampling. The Likert scale questionnaire instrument (1-5) was analyzed using SPSS for descriptive statistics, validity/reliability tests, simple linear regression, t-test, and R². The results showed a significant positive effect (t-count 5.370 > t-table 2.034; sig. 0.000), with R² 0.450 which means leadership explains 45% of the performance variation. The conclusion states that chief engineers need to implement proactive leadership to improve shipping efficiency and safety.